The system of formation and evaluation of the information of cash flows - Mackevičius, Jonas; Senkus, Kastytis (Journal of Business Economics and Management, 2006)
A very urgent problem of formation of cash flows in conditions of the competitive market is considered in the present article. Cash flows are defined as the inflows and outflows of cash and cash equivalents, created within a certain period of time out of the operating, financial, investment and extraordinary activities of the company. Examples of cash flows out of the operating, financial and investment activities of the company are adduced. The system of formation and evaluation of the information about cash flows is created. Its principal elements are as follows: cash flow accounting, classification of cash flows, issuing of the cash flow statement, control and analysis of cash flows, cash flow forecasting. The methods of analysis of cash flows are created, i.e. the horizontal analysis of the cash flow statement; the vertical analysis of the cash flow statement; the analysis of financial ratios of the cash flow statement; preparation of the cash flow forecast. Practical application of the system of formation and evaluation of the information about cash flows would help the company managers to take various management decisions on evaluation of the company’s financial condition and its activity results better, quicker and more precisely. Firstd Published Online: 14 Oct 2010